Endovascular stenting for extracranial carotid artery aneurysms: Experiences and mid-term results. Issue 46 (November 2016) - Ni, Leng; Pu, Zuo; Zeng, Rong; Zhang, Rui; Zheng, Yue-hong; Ye, Wei; Liu, Chang-Wei
Abstract : Abstract: The aim of this study was to investigate the safety and effectiveness of endovascular stenting for extracranial carotid artery aneurysms (ECAAs) and evaluate the mid-term outcomes. Twelve consecutive symptomatic patients (mean age 43.8 ± 14.9 years; 8 men) with ECAAs who were treated with endovascular stenting between 1997 and 2015 were retrospectively analyzed. Clinical follow-up data including symptoms and neurological events were obtained from outpatient records. Imaging follow-up with duplex ultrasound and/or computed tomographic angiography (CTA) was performed to examine the aneurysm obliteration and patency of the stents at 3, 6, 12 months and yearly thereafter. A total of 5 true aneurysms and 7 pseudoaneurysms were included in our series. Neurological symptoms (n = 5, 41.7%) and a pulsatile neck mass (n = 5, 41.7%) were the most common presenting symptoms. Endovascular stenting procedures were technically successful in all cases; 3 patients received bare stents, and 9 patients received covered stents. No perioperative neurologic or cardiopulmonary complications occurred. Over a period of follow-ups (mean 21.8 ± 25.1 months), all patients were alive and free from neurological or other adverse events. All aneurysms were completely excluded except for 1 patient who was exposed to a residual medium leaking into the aneurysm sac. No reintervention was performed in this specific patient because aneurysm growth or significant clinical symptoms did not occur. Recurrent restenosis assessed by CTA imaging at 12 months occurred in 1 (8.3%) patient in our series. Target lesion revascularization for this hemodynamic restenosis was treated with placement of an additional stent. In our series, endovascular stenting for ECAAs was found to be safe, effective, and proved to have promising mid-term results. Although long-term results need to be further explored, advantages including less procedure-related complications and a shorter recovery time make endovascular stenting an attractive option for ECAAs, especially for the patients who are unfit for traditional open surgery.